Combined effects of high-intensity focused electromagnetic therapy and pelvic floor exercises on pelvic floor muscles and sexual function in postmenopausal women - Saher Lotfy Elgayar (Korean Society of Obstetrics and Gynecology, 2024)
Objective This study aimed to explore the impact of high-intensity focused electromagnetic therapy (HIFEMT) on the pelvic floor muscles (PFM), sexual function, and quality of life (QoL) among postmenopausal women. Methods Fifty postmenopausal women with PFM weakness and sexual dysfunction were randomly allocated into two equal groups. The HIFEMT group participated in the PFM training program in addition to HIFEMT, whereas the control group performed PFM training only. For 12 weeks, HIFEMT was scheduled twice a week, while PFM training was performed daily. At baseline and after 12 weeks, PFM strength and endurance were assessed using a perineometer, sexual function was examined using the female sexual function index (FSFI), and QoL was assessed through the menopause-specific quality of life questionnaire (MENQOL). Results The HIFEMT and control groups showed significant increases in PFM strength and endurance and FSFI scores, and significant declines in MENQOL compared with baseline measures (P<0.05). Compared to the control group, the HIFEMT group showed substantial improvements in all measured variables after 12 weeks (P<0.05). Conclusion Addition of HIFEMT to PFM training improved the PFM strength, endurance, sexual function, and QoL in postmenopausal women with PFM weakness and sexual dysfunction.